Advances in functional training - Boyle, M.; Verstegen, M.; Cosgrove, A. (Lotus Publishing, 2010)
Functional Training for Sports, new understanding of functional anatomy created a shift in strength coaching. With this new material, Coach Boyle presents the continued evolution of functional training as seen by a leader in the strength and conditioning field. Mark Verstegen, founder and president of Athletes' Performance, is a widely sought-after performance coach, consultant, and motivational speaker. Alwyn Cosgrove is a columnist for "Men's Fitness" and a highly respected strength and conditioning coach. He has worked with Olympic and national-level athletes, five World Champions, and professionals in many sports.